The HUBUNGAN AKTIVITAS FISIK DENGAN KUALITAS TIDUR PADA SISWA KELAS X IPA 2 DI SMA NEGERI 1 KOTO GASIB - Vai, Aref; Adila, Fekie; Nita Wijayanti, Ni Putu Nita Wijayanti; Sulastio, Agus; Ittaqwa, Ittaqwa; faujiah, faujiah (Pusat Pengembangan Olahraga Universitas Pahlawan, 2024)
Some efforts to maintain health are by doing physical activity and maintaining quality sleep. The purpose of this study was to determine whether there is a relationship between physical activity and sleep quality in class X IPA 2 SMA Negeri 1 Koto Gasib. This research is a type of correlational research. The sample in this study consisted of 25 students of class X IPA 2. Data collection to determine the level of physical activity of students was obtained from completing the The Physical Activity Questionnaire for Adolescents (PAQA) questionnaire, while to determine the level of students' sleep quality was obtained from filling out the Pittsburgh Sleep Quality Index ( PSQI) questionnaires were given directly to students and then data analysis was carried out. and hypothesis testing using the parametric statistical method Pearson's Product-Moment Correlation Coefficient. The results found in this study were 7 (28%) students whose physical activity was included in the moderate category, and 18 (72%) students who were included in the low category, then there were 11 (44%) students with good sleep quality and 14 students . (56%) students with poor sleep quality. The results of data analysis obtained rx.y = 0.569, and rx.y = 0.569 > r table: 0.505. Based on the results of this study, the level of association of 0.569 is at the